State Support for Illinois Public Universities Intercollegiate Athletics Programs. Item #3. - Illinois State Board of Higher Education, Springfield; Illinois State Board of Higher Education, Springfield ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
This report considers the various sources of support for intercollegiate athletics programs at Illinois public universities including direct state appropriations, tuition revenue foregone through student tuition waivers, and athletic fees supported by the Monetary Award Program. It reports that in fiscal year 1992, state support for intercollegiate athletics totalled approximately $12.9 million, including $7.4 million in direct state appropriations, $3.3 million in tuition waivers, and $2.1 million in fees covered by the Monetary Award Program of the Illinois Student Assistance Commission. The report suggests that the elimination of direct state-appropriated support for intercollegiate athletics will allow public universities to reinvest over $7 million per year to higher priority activities. Additionally, Illinois public universities should consider various productivity improvements to assure that they are offering high quality, cost effective intercollegiate athletics programs. Each institution also should examine the relationship of its intercollegiate athletic program to its mission and other institutional needs and priorities. Statistical tables concerning expenditures for intercollegiate athletics constitute much of the report. (GLR)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Athletics; Expenditures; Fees; Financial Support; Higher Education; Intercollegiate Cooperation; Public Colleges; State Aid; Tuition; Illinois; Reports, Evaluative